Effects of Repetition Suppression on Sound Induced Flash Illusion With Aging - Sun, Yawen; Liu, Xiaole; Li, Biqin; Sava-Segal, Clara; Wang, Aijun; Zhang, Ming (Frontiers in Psychology, 2020)
The sound-induced flash illusion (SiFI) is a classical auditory-dominated multisensory integration phenomenon in which the observer misperceives the number of visual flashes due to the simultaneous presentation of a different number of auditory beeps. Although the SiFI has been documented to correlate with perceptual sensitivity, to date there is no consensus as to how it corresponds to sensitivity with aging. The present study was based on the SiFI paradigm (Shams, Kamitani, & Shimojo, 2000), adding repeated auditory stimuli prior to the appearance of audiovisual stimuli to investigate the effects of repetition suppression (RS) on the SiFI with aging. The repeated auditory stimuli consisted of one or two of the same auditory stimuli presented twice in succession, which were then followed by the audiovisual stimuli. By comparing the illusions in old and young adults, we aimed to explore the influence of aging on the RS of auditory stimuli on the SiFI. The results showed that both age groups showed SiFI effects; however, the RS performance of the two age groups had different effects on the fusion and fission illusions. The illusion effect in old adults was weaker than in young adults. Specifically, RS only affected fission illusions in the old adults but both fission and fusion illusions in young adults. Thus, the present study indicated that the decreased perceptual sensitivity based on auditory RS could weaken the SiFI effect in multisensory integration and that old adults are more susceptible to RS, showing that old adults perceived the SiFI effect weakly under auditory RS.